Pengaruh Lingkungan Situasional Terhadap Pemilihan Tempat Belanja Minimarket di Kota Denpasar - Sukmantara, Wayan; Sri Suprapti, Ni Wayan (E-Jurnal Manajemen, 2014)
Situational environment is one of trigger that can affect consumer behavior. That contains five characteristics that each characteristic have different effect to make consumer choosing a place to shopping. The purpose of this research is to know how major difference and the probability among situational environment affect consumer in Denpasar to choosing Minimarket as their main-shopping place. This research use 150 respondent that have been decided by purposive sampling technique. The method that used in this research is descriptive and inference statistic, such as logistic regression. The result of this research showed that situational environment have partial effect to choosing Minimarket in Denpasar and have a variant possibilities on each situational characteristics.
Keywords: Situational Environment; Choosing Shopping Place; Social Environment